Gestão da inovação aberta: mitigação do risco no processo de acesso à inovação - Fontão, Henio (2012)
This research discusses the knowledge about one of the processes of open innovation system, such as the technological access. In this research, we aim to identify a combination of factors with minor level of associated risk, based on the inferential observations of technological risks and corporative about the innovative performance of twenty eight companies with technological base located in Brazil. In synthesis, the proposition of the research is centered in the importance of these companies to manage risks that influence in the innovation processes. The objective of the research was to propose an efficient model for the mitigation of risks in the processes of access to external sources of technological innovation, as part of a management model of open innovation processes. Experimental, statistical and inferential method, was used to collect data in observational situation, once, none of the studied variables were under the control of the researcher. In order to fulfill the general goal, two models were presented: one empirical and another generic. Empiric evidences were found to testify the influence and significance of elements of open innovation to maximize the corporative results. Among these elements, are: the development of partnership with universities and other research centers, the risk of underinvestment in internal and external R&D and the risk of absence of intellectual property. The results also demonstrated that the companies could not maximize totally and simultaneously all the results individualized; so the need of a broad management under the conditionals factors of the best answers and expected results. Moreover, the empirical model allows to the managers to take decisions, from the compatibility of factors that integrate the group of better risk profiles to the diverse expected answers. Based on their feature of probabilistic and generalization, the proposed models contributed promptly, demonstrating to the technology-based companies, the level of risk that must be accepted as condition to the achievement of better results with innovation and, consequently, to access external sources of innovation with minor associated risk.